Analysis of Entry Modes and Competitive Strategies for Foreign Banks in Post-WTO China - Huang, Yuwei (2006)
This dissertation aims to study and analyze the entry modes and competitive strategies for foreign banks in post-WTO China. Firstly China's banking system and China's WTO commitments to open up its banking sectors are generally reviewed. Then use the PEST and SWOT analysis methods to examine the external and internal factors which have influences on foreign banks' strategies. Combined the theories with the practical situations of the chosen entry modes and competitive strategies by foreign banks, it is found that there is any fixed or standard entry mode and operating strategy for those foreign banks. Every mode and strategy has its own strengths and restrictions. Therefore, foreign banks seeking successful operation in China should make the proper decision depending on their own conditions and operating objectives.